New fossil Anaxyelidae (Insecta: Hymenoptera: Siricoidea) from the Lower Cretaceous Yixian Formation of northeastern China - Li, Yi; Rasnitsyn, Alexandr P.; Shih, Chungkun; Ren, Dong; Wang, Mei (Zootaxa, 2024)
One new genus and two new species, Hemisyntexis lepida gen. et sp. nov., Eosyntexis conflata sp. nov., and new material of Parasyntexis khasurtensis Kopylov, 2019 are respectively described and illustrated based on three well-preserved compression fossils from the Lower Cretaceous Yixian Formation of northeastern China. Eosyntexis conflata sp. nov., placed in the genus Eosyntexis Rasnitsyn, together with H. lepida, belongs to the subfamily Syntexinae of Anaxyelidae. The new species provide important morphological characters to enhance our understanding of the subfamily Syntexinae, and to revise the diagnostic characters of Eosyntexis as well. Moreover, we carried out a comprehensive survey of all currently published extant and extinct species of Anaxyelidae to gain a better understanding of the trend of change for the forewing and body length. Furthermore, we formally documented that the Anaxyelidae had four different color patterns for the wings simultaneously in the Jehol Biota of the Lower Cretaceous.